2011
DOI: 10.1089/jmf.2011.1626
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects ofHaematococcusAstaxanthin on Oxidative Stress in Healthy Smokers

Abstract: Free radicals induced by cigarette smoking have been strongly linked to increased oxidative stress in vivo, contributing to the pathobiology of various diseases. This study was performed to investigate the effects of Haematococcus astaxanthin (ASX), which has been known to be a potent antioxidant, on oxidative stress in smokers. Thirty-nine heavy smokers (≥20 cigarettes/day) and 39 non-smokers were enrolled in this study. Smokers were randomly divided into three dosage groups to receive ASX at doses of 5, 20, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 25 publications
2
33
0
Order By: Relevance
“…; Kim et al . ). Based on a study conducted on 33 healthy volunteers, Aquasearch Inc. () disclosed no toxicity or ill effects attributable to the daily ingestion of either 3.85 mg (low dose) or 19.25 mg (high dose) of algal astaxanthin derived from H. pluvialis for 29 consecutive days as analysed by clinical and medical parameters.…”
Section: Safety Of Astaxanthinmentioning
confidence: 97%
“…; Kim et al . ). Based on a study conducted on 33 healthy volunteers, Aquasearch Inc. () disclosed no toxicity or ill effects attributable to the daily ingestion of either 3.85 mg (low dose) or 19.25 mg (high dose) of algal astaxanthin derived from H. pluvialis for 29 consecutive days as analysed by clinical and medical parameters.…”
Section: Safety Of Astaxanthinmentioning
confidence: 97%
“…In smoker subjects the Haematococcus astaxanthin supplementation had reduced levels of oxidative stress biomarkers, and for some of these the decreasing was dose-dependent, showing the role of this nutrient in preventing oxidative damage induced by cigarette smoking [38]. Regarding the antioxidant power and the free radical scavenger activity, the astaxanthin can be considered more effective than β -carotene and lycopene [39].…”
Section: Carotenoids and Cardiovascular Healthmentioning
confidence: 99%
“…Astaxanthin has attracted a great deal of attention due to its multiple functions and antioxidant potential, which have been reported to surpass those of β‐carotene or lutein, even α‐tocopherol (Naguib ; Kim et al . ). Some studies demonstrated that dietary astaxanthin could increase the total antioxidant capacity (TAS) and improve growth performance of black tiger shrimp Penaeus monodon (Thongrod et al .…”
Section: Introductionmentioning
confidence: 97%